ANALISIS REPRESENTASI MATEMATIS SISWA DALAM MEYELESAIKAN PERMASALAHAN PROGRAM LINEAR DI SMA NEGERI MODEL TERPADU MADANI PALU - I Gede Darma Wisilayasa; Mustamin Idris; Ibnu Hadjar (Jurnal Elektronik Pendidikan Matematika Tadulako, 2022)
This study aims to obtain a description of the results of student representation in solving linear programming problems at SMA Negeri Model Terpadu Madani Palu. This type of research is descriptive with a qualitative approach. The research subjects were selected based on the results of the students' mathematical ability tests which were then categorized based on high, medium and low mathematical abilities. The results of this study indicate that (1) Regarding the mathematical representation of the symbol form of students in the category of high mathematical ability (KST) (MD), students with the category of moderate mathematical ability (KSS) (NS) and students with low mathematical ability (KSR) (MF). ) is able to make equations, algebraic symbols, mathematical operations, mathematical models and solve problems involving mathematical expressions well. (2) In visual form, students both KST (MD), KSS students (NS) and KSR students (MF) have been able to present data or information from a representation to a graphical representation. While in tabular form, KSR students (MF) did not use tables to clarify problems and facilitate solutions. (3) Verbally KST students (MD) can write down the steps for solving math problems in words and answer questions using written or spoken text and draw conclusions correctly. Likewise, KSS students (NS) can also make good conclusions. However, KSR (MF) students for verbal representation are still lacking, KSR (MF) students rarely use and clarify solutions with verbal words or sentences and are often wrong in explaining the answers they get.